Solid-State Fermentation to Improve the Nutrient Value, Supplementation Level, and Digestibility of Palm Kernel Meals as Feed Ingredients for Red Nile Tilapia (Oreochromis niloticus) - Siti Lusi Arum Sari; Triyanto Triyanto; Zuprizal Zuprizal; Irfan Dwidya Prijambada (HAYATI Journal of Biosciences, 2026)
This study investigated the potential of palm kernel meal (PKM) as a sustainable feed ingredient for red tilapia. Palm kernel meal is a byproduct of palm oil production, abundant in Indonesia. Like other plant-based feed ingredients, PKM contains a lot of non-starch polysaccharides (NSP), making it difficult to digest, especially for monogastric animals. This study aimed to improve the nutritional value, digestibility, and dietary supplementation levels of PKM for red tilapia through solid-state fermentation (SSF). PKM was fermented using Paenibacillus polymyxa BR25, a fibrolytic bacterium isolated from the buffalo rumen. SSF enhanced the nutritional value of PKM, as indicated by an increase in dry matter, crude protein, calcium, phosphorus, and ash. Essential amino acids, including threonine and methionine+cysteine, were also increased, accompanied by decreases in hemicellulose and cellulose, indicating effective NSP degradation. In addition, oleic acid and linoleic acid increased, providing essential fatty acids for fish health and development. Unfermented PKM negatively affected growth at inclusion levels up to 10%, whereas fermented PKM maintained growth performance at a 15% dietary inclusion. In addition, SSF significantly increased the digestibility of dry matter, protein, and lipid in tilapia, demonstrating its potential to enhance PKM utilization in aquafeeds.